A COMPARATIVE STUDY ON THE REMOVAL OF REMAZOL GOLDEN YELLOW 6 DYE BY MIXED CULTURE OF DEAD FUNGAL BIOMASS AND ACTIVATED CARBON - Fadjari Lucia Nugroho (Purifikasi, 2008)
Remazol Golden Yellow 6 is a vinyl sulfone reactive dye with an azo-based chromophore, which produces a coloured wastewater that is difficult to treat by biological treatment. Physical adsorption of coloured wastewaters with activated carbon although effective is economically expensive. It is therefore necessary to find effective and economic alternatives for absorbant, such as microorganisms. The biosorption capacity of a mixed culture of dead fungi biomass (Aspergillus sp., Penicillium sp., and Saccharomyces sp.) for Remazol Golden Yellow 6 was examined as a function of initial pH and initial dye concentration. The results were compared to the adsorption capacity of a commercial activated carbon. Optimum initial biosorption pH was determined as 1. The percent dye removal of 0.5 g biomass with initial dye concentrations of 60 mg/l, 80 mg/l and 100 mg/l were 90.3%, 93.6% and 97.6% respectively with equilibrium established within 75, 125 and 150 minutes. In comparison, dye removal with granular activated carbon for the same dye concentrations were respectively 32.1%, 36.4% and 37.8 % with equilibrium time at 275, 400 and 475 minutes.